Тhe impact of the Covid-19 epidemic on older adults’ experiences with healthcare services - Shinan-Altman, Shiri; Levkovich, Inbar; Porat, Amit; Alperin, Mordechai (Ревија за социјална политика/Journal of Social Policy, 2020)
Objective: Maintaining healthcare services consumption as needed during a pandemic crisis is important, in general, and specifically for older adults. Therefore, the current study aimed to examine factors associated with experiences related to healthcare services among Israeli older adults during the COVID-19 pandemic. Methods: A cross-sectional online survey was conducted among 261 older adults (aged 60+). Participants completed measures of perceived health status, COVID- 19 perceived risk, knowledge about COVID-19, depression, coping resources, experiences with healthcare services (contact with a family physician, fear of contracting the virus via direct contact with the healthcare system). Two multiple regressions were calculated for the following dependent variables: contact with a family physician during COVID-19, and fear of contracting the virus via direct contact with the healthcare system during COVID-19. Results: Older adults’ contact with a family physician during COVID-19 was lower than their contact prior to the pandemic. A higher extent of contact with a family physician during COVID-19 was related to higher knowledge about COVID- 19. In addition, a higher extent of fear of contracting the virus via direct contact with the health system during COVID-19 was related to lower years of education, higher COVID-19 perceived risk, and lower knowledge about COVID-19. Conclusions: The results could provide public health policymakers with a more complete picture of the impact of the COVID-19 crisis among older adults. This study highlights the characteristics and factors that encourage/discourage older adults from seeking healthcare services during a virus outbreak, such as the COVID- 19 pandemic.